Kinerja Manajerial dan Persepsi Nasabah Terhadap Perbankan Syariah di Jawa Barat - R. Hozin Abdul Fatah; Sugeng Setyadi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
The research reveals the performance of Islamic banking in West Java with emphasis on the role of banking intermediation in terms of managerial and customer persefsi terhdap Islamic banks. There are two findings revealed that the performance of Islamic banking of managerial and explore public perception (customers and non-customers) and its response to Islamic banking. Achievement of the performance of Islamic banking in terms of managerial aspects with an average index performance index of 78.05. Not optimal managerial performance because the Islamic banking; not optimal accommodate the wishes and needs of customers and society due to limited facilities, product innovation is still low, and the lack of transparency in the sharing system. Judging from the general public perception is already relatively well. Cognitive aspect shows customers already understand terahadap Islamic banking because it has good access to information so they can create awareness (awareness). The communities also tend to like Islamic banking and to support efforts to socialize the banks and the public has not become a customer intends to become a customer. Only selection Islamic banking is still dominated by the state-owned Islamic banking choice because it is considered bona fide. The study also found differences in the perception of the Bank Umum Syariah versus BPR Syariah. The correlation value is obtained to reach .987. That is a decision the community (customers and non-customers) 98.7% influenced by their perceptions of Islamic banking while the rest (1.3%) is influenced by other variables not included in the model.